Pengaruh Pola Pikir Spiritual Dan Keseimbangan Gender Terhadap Transformasi Wirausaha Di Kota Batu: Pola Pikir Spiritual, Keseimbangan Gender, Transformasi, Wirausaha - Indah, Sri; Himawan Wibisono, Sukarno (Jurnal Paradigma Ekonomika, 2024)
This study aims to investigate the influence of spiritual mindset and gender balance on the transformation into an entrepreneur. Using a quantitative approach, data will be collected from respondents in Batu City through questionnaires and interviews. The questionnaire will measure the factors of spiritual mindset, gender balance and entrepreneurial transformation. Data analysis will use multiple regression to determine whether spiritual mindset and gender balance significantly influence decisions and steps in the entrepreneurial process. It is hoped that this study can provide a deeper understanding of the psychological and social factors that influence entrepreneurial transformation, as well as provide a basis for the development of more inclusive and sustainable entrepreneurial policies and practices. Through these results, it is hoped that this study can make a significant contribution to the academic literature on entrepreneurship and support inclusive and sustainable economic development. The results of the study indicate that there is a significant influence of spiritual mindset and gender balance on entrepreneurial transformation in SMEs in Batu City.